Nosocomial suicide. (April 2014) - Large, Matthew; Ryan, Christopher; Walsh, Gerard; Stein-Parbury, Jane; Patfield, Martyn
Objective and Method: To consider the possibility that adverse aspects of psychiatric hospitalisation may precipitate suicide contributing significantly to the increased rate of suicide among inpatients, given little has been published about this. Results and Conclusions: It is likely that psychiatric hospitalisation itself contributes to some inpatient suicides. This has significant implications for the delivery of inpatient psychiatric care.